PENGARUH PROGRAM TAYANGAN INFOTAINMENT DI TELEVISI TERHADAP PERSEPSI IBU RUMAH TANGGA TENTANG FENOMENA PERCERAIAN DI KELURAHAN LIMBUNGAN KECAMATAN RUMBAI PESISIR PEKANBARU - Nurul Anissa; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Infotainment progran these days on many television station are rated negatively impact that could be effected to behaviour and lifesyle of the people. When infotainment program all serving divorce news, the statistic divorce among people also increased. And when infotainment also popularizing issues about affair, it turns out the affair also happened among people that brought them to divorce household. Based on demographic segments, infotainments audience more dominated by middleaged woman especially the housewifes. The purpose of this research was to analyze the influence of infotainment program on television of housewife perception about divorce phenomenon at Limbungan Village Rumbai Pesisir Distirict Pekanbaru City.The method that used in this reaseacrh is quantitative method. Data collection using observation, questionnaries and documentation. To determine the effect of the influence of infotainment program on television of housewife perception about divorce phenomenon at Limbungan Village Rumbai Pesisir Distirict Pekanbaru City, the authors used simple linear regression analysi. The variable X in this reasearch were Infotainment Program on television, while the variable Y is housewife perception about divorce phenomenon at Llimbungan Village Rumbai Pesisir Distirict Pekanbaru City. Number of samples in this research were 97 people by using purposive sampling technique. Data processing trials conducted using questionnaries Statistic Program Product abd Service Solutions (SPPS) Windows version 20.The results of this research shows the influence of infotainment program on television of housewife perception about divorce phenomenon at Limbungan Village Rumbai Pesisir Distirict Pekanbaru City. It is based on the analysis of the data using a simple linear regression is Y = 0,378 + 0,897 X. With the t count 75,297 bigger when compared to t table 1,985 and 0,000 significance level less than = 0,05, therefore H1 accepted. Impressionsnof nfotainment program on television 98,4% influence on housewife perceptonat Limbungan Village, the remaining 1,6% is caused by another factor out of this reasearch. Therefore there is a significant effect between infotainment program on television of housewife perception about divorce phenomenon at Limbungan Village Rumbai Pesisir Distirict Pekanbaru City.Keyword : Infotainment, Housewife, Perceptio, Limbungan Village